Selective HCN1 block as a strategy to control oxaliplatin-induced neuropathy. (15th March 2018) - Resta, F.; Micheli, L.; Laurino, A.; Spinelli, V.; Mello, T.; Sartiani, L.; Di Cesare Mannelli, L.; Cerbai, E.; Ghelardini, C.; Romanelli, M.N.; Mannaioni, G.; Masi, A.
Abstract: Chemotherapy-Induced Peripheral Neuropathy (CIPN) is the most frequent adverse effect of pharmacological cancer treatments. The occurrence of neuropathy prevents the administration of fully-effective drug regimen, affects negatively the quality of life of patients, and may lead to therapy discontinuation. CIPN is currently treated with anticonvulsants, antidepressants, opioids and non-opioid analgesics, all of which are flawed by insufficient anti-hyperalgesic efficacy or addictive potential. Understandably, developing new drugs targeting CIPN-specific pathogenic mechanisms would dramatically improve efficacy and tolerability of anti-neuropathic therapies. Neuropathies are associated to aberrant excitability of DRG neurons due to the alteration in the expression or function of a variety of ion channels. In this regard, Hyperpolarization-activated Cyclic Nucleotide-gated (HCN) channels are overexpressed in inflammatory and neuropathic pain states, and HCN blockers have been shown to reduce neuronal excitability and to ameliorate painful states in animal models. However, HCN channels are critical in cardiac action potential, and HCN blockers used so far in pre-clinical models do not discriminate between cardiac and non-cardiac HCN isoforms. In this work, we show an HCN current gain of function in DRG neurons from oxaliplatin-treated rats. Biochemically, we observed a downregulation of HCN2 expression and an upregulation of the HCN regulatory beta-subunit MirP1. Finally, we report the efficacy of the selective HCN1 inhibitor MEL57A in reducing hyperalgesia and allodynia in oxaliplatin-treated rats without cardiac effects. In conclusion, this study strengthens the evidence for a disease-specific role of HCN1 in CIPN, and proposes HCN1-selective inhibitors as new-generation pain medications with the desired efficacy and safety profile. Highlights: Nociceptive neurons from oxaliplatin-treated rats show Ih gain of function. Increased current density is mediated by HCN1-specific kinetic enhancement. Acceleration of HCN1 kinetics is associated to increased MiRP1 expression. Pan HCN blockers effectively revert neuropathy in vivo but cause bradycardia. HCN1-selective blocker MEL57A shows intact analgesic efficacy without cardiac effects.